The Educational Value and Practical Path of Cross-Regional Study Tours: A Case Study of Shanghai-Mongolia Study Tours - 杜月 (Education Research on Study Tours and Practice, 2025)
As an innovative educational form that integrates learning and travel, study tours are a necessary supplement to traditional classroom education and have been widely welcomed across the country in recent years. This paper analyzes two cases of Shanghai-Mongolia study tours, namely "The End of the Sea is the Grassland" and "The Journey - From Grassland to Sea", conducted by the Inner Mongolia Natural History Museum and the Shanghai Science and Technology Museum from 2023 to 2024. It elaborates on how museums can utilize cross-regional resources and adopt contextualized curriculum design ideas to explore new practical activities for study tours. It also proposes three elements: integrating differentiated resources, designing contextualized activities, and coordinating multiple stakeholders, with the aim of establishing a new museum study tour model that integrates "natural ecology, historical culture, and ethnic emotions", thereby breaking the traditional spatial limitations of educational activities and providing some reference viewpoints for developing cross-regional study tour products.